The association between different types of childhood trauma and orthorexia nervosa: an observational study - Pesavento, Francesca; Rossi, Alessandro Alberto (Frontiers in Psychology, 2025)
ObjectiveOrthorexia Nervosa (ON) is characterized by the pursuit of perfect eating, leading to severe physical, psychological, and social problems. Although not yet formally recognized as an official diagnosis, ON shares etiological factors with traditional eating disorders, such as adverse childhood experiences (CT). This study explores the association between different CT types and ON, a relationship scarcely investigated in the literature.MethodsA sample of 175 participants (age 18–74 years, M = 44.10; SD = 12.85) completed the Italian Düsseldorf Orthorexia Scale (I-DOS) and the Childhood Trauma Questionnaire (CTQ-SF), assessing Physical Abuse (PA), Emotional Abuse (EA), Sexual Abuse (SA), Physical Neglect (PN), and Emotional Neglect (EN). A backward linear regression analysis investigated the CT-ON association.ResultsThe regression model explained 7.8% of variance in ON. EA emerged as the strongest predictor. SA showed limited relevance. The negative association with PA likely reflects statistical suppression effects and should be interpreted with caution. PN and EN showed positive but non-significant associations with ON.ConclusionThese findings support the role of CT, particularly EA, in ON development. EA represents the most clinically relevant trauma type, suggesting therapeutic interventions should prioritize addressing emotional abuse. However, the modest variance explained indicates that future studies should investigate additional psychological factors (e.g., perfectionism, cognitive restraint, attachment) to gain comprehensive understanding of ON etiology. This exploratory study provides foundational knowledge for future research on CT’s role in ON.